RELE PROTEKSI GANGGUAN GENERATOR 65 MW PADA PLTU PT. PLN (PERSERO) TANJUNG ENIM - Fery Antony (Jurnal Informatika Global)
Protection system is  essential for generating power. This protection is designed to protect and minimize the damage that occurs when the disorder. Plant protection system should work according to condition quickly react in the event of disruption, selective, sensitive / insensitive to interference, reliable / reliability, stability and economical. If the conditions are not met, it will affect the performance of the plant. Generator protection system also aims to protect the generators electric service reliability and continuity. With the achievement of system reliability and efficiency are met.  Keywords : Generato Protection, Relay Protection